Rekonstruksi Model Kepemimpinan Profetik Amos dan Mikha tentang Etika dan Karakter Pemimpin Kristen - Debora Yustina Dewi Pitaloka; Anon Dwi Saputro (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2026)
This article reconstructs the prophetic leadership model of Amos and Micah as a foundation for ethics and the character of Christian leaders. The background highlights the need to build church leadership capable of addressing contemporary social and spiritual challenges through leaders who are grounded in character and ethical conduct. The method employed is a literature review and textual theological analysis to examine the leadership styles of these two minor prophets. The discussion shows that Amos’ leadership emphasizes courage and decisiveness in upholding social justice, while Micah stresses character formation through fidelity and humility. The integration of these approaches yields a prophetic leadership model that is holistic and applicable to the modern Christian service context. The study presents an integration of two leadership styles that were previously often examined separately. The study recommends further research to test the implementation of this model in church leadership training and its impact on leadership regeneration and service performance.